Investasi Asing Dalam Pendirian PT Perorangan Ditinjau Dari UUPT Dan UU Cipta Kerja - Siti Isnaeni Ramadhani; Kharisma Ladyagustina; Sumriyah Sumriyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The purpose of this study is to examine foreign investment owned by individual companies. This study uses normative legal research methods. Legal and conceptual approaches are the approaches used in this research. The collection of legal materials in this journal uses library research. The legal material analysis method used in this journal refers to deductive, namely drawing conclusions from a problem that is general in nature to the concrete problems faced. Namely explaining things that are general to matters that are specific in order to draw conclusions that can provide answers to the problem of this research, namely regarding investment in the establishment of individual PT in UUPT and UU Cipta Kerja. The results of this study show that after the promulgation of the Job Creation Law which changed several provisions in the Company Law, one of them introduced a new form of legal entity, namely an Individual Company which is specifically for MSEs with the aim of forming it to facilitate the development of micro and small businesses by being able to form legal entity business entities. only with 1 (one) founder or shareholder. Investment is basically an activity for a fairly long period of time, so that when investors' investment interest declines, the role of the government in inviting investors to invest in Indonesia will be able to help attract investors' interest and the impact will be felt when the process of economic activity has been running and there has been an increase in economic value.